HU-Lacking Mutants of Salmonella enterica Enteritidis Are Highly Attenuated and Can Induce Protection in Murine Model of Infection - Milanez, Guilherme P.; Werle, Catierine H.; Amorim, Mariene R.; Ribeiro, Rafael A.; Tibo, Luiz H. S.; Roque-Barreira, Maria Cristina; Oliveira, Aline F.; Brocchi, Marcelo (Frontiers in Microbiology, 2018)
Salmonella enterica infection is a major public health concern worldwide, particularly when associated with other medical conditions. The serovars Typhimurium and Enteritidis are frequently associated with an invasive illness that primarily affects immunocompromised adults and children with HIV, malaria, or malnutrition. These serovars can also cause infections in a variety of animal hosts, and they are the most common isolates in poultry materials. Here, we described S. Enteritidis mutants, where hupA and hupB genes were deleted, and evaluated their potential use as live-attenuated vaccine candidates. In vitro, the mutants behaved like S. Typhimurium described previously, but there were some particularities in macrophage invasion and survival experiments. The virulence and immunogenicity of the mutant lacking both hupA and hupB (PT4ΔhupAB) were evaluated in a BALB/c mice model. This mutant was highly attenuated and could, therefore, be administrated at doses higher than 109 CFU/treatment, which was sufficient to protect all treated mice challenged with the wild-type parental strain with a single dose. Additionally, the PT4ΔhupAB strain induced production of specific IgG and IgA antibodies against Salmonella and TH1-related cytokines (IFN-γ and TNF-α), indicating that this strain can induce systemic and mucosal protection in the murine model. Additional studies are needed to better understand the mechanisms that lead to attenuation of the double-mutant PT4ΔhupAB and to elucidate the immune response induced by immunization using this strain. However, our data allow us to state that hupAB mutants could be potential candidates to be explore as live-attenuated vaccines.